Gall bladder perforation; occurrence, clinical presentation, diagnosis and their outcome: a retrospective study in a tertiary care hospital in South India - Ramachandra, M. L.; Jabbar, Faiyaz Abdul (International Surgery Journal, 2019)
Background: Gall bladder perforation (GBP), is an uncommon complication of acute cholecystitis but it often remains a cause for diagnostic dilemma among surgeons while managing patients presenting with signs and symptoms of peritonitis. This study was undertaken to study the clinical profile of the patients diagnosed to have GBP which would aid in early diagnosis and surgical intervention thus improving the patient’s outcome. Methods: A retrospective study from May 2013 to April 2018 with a sample size of 12 cases were studied. All cases were diagnosed either pre-operatively (based on radiological findings) or intra-operatively. Perforations of gall bladder caused due to trauma or iatrogenic reasons were excluded from the study. Intra-operative findings, post-operative sequelae and the outcome of the patient were evaluated. Results: The mean age of the patients was 66 and females were more affected than the males. USG done preoperatively could pick up only 1 out of 12 cases. Whereas CT showed gall bladder perforation in 3 out of 4 cases for whom CT was done giving it a sensitivity of 75%. Gall bladder perforation was commonly found to be located in the fundus followed by corpus and infundibulum. Conclusions: GBP is a rare complication of acute cholecystitis. It can present with full blown peritonitis features or vague abdominal symptoms. If promptly diagnosed and treated aggressively by laparotomy and cholecystectomy, the patient’s outcomes are improved.